Phenomenological Review of Coach’s Perceptions of the Karate Oath as an Instillation of Character Education - Baehaqi, Mochamad Rafli; Alif, Muhammad Nur; Supriyadi, Tedi (Universitas Negeri Semarang, 2024)
Karate is a sport that is quite popular among students, so this sport has a strategic role in educating students. One form of education in karate is character formation. This research highlights the role of the karate oath as a solution to deepen physical education by including affective attitudes. The phenomenological research method was used to understand the coach's subjective experience regarding the karate oath as a tool for forming character. Data was collected through semi-structured interviews with six experienced coaches at Chexo'z Karate Club. Data analysis was done using a data reduction, presentation, and conclusion approach. The research revealed that coachs view the karate oath as more than just a set of words but a powerful tool for forming mental attitudes, discipline, and character values such as integrity, patience, and respect. These findings provide in-depth insight into how the karate oath is internalized and applied by coaches in the context of student character formation in karate clubs. The implications of this research can contribute to developing training programs to strengthen students' character dimensions in karate training and stimulate further discussion about the role of oaths in character education through combat sports.